Investigation of Impact of Irrigation of Distillery Spentwash on the Nutrients of Pulses - Chandraju, S.; Basavaraju, H.C.; Chidan Kumar, C.S. (Asian Journal of Chemistry, 2010)
Cultivation of pulses was made by irrigation with distillery spentwash of different proportions. The distillery spentwash i.e., primary treated spentwash, 50 % and 33 % distillery spentwash were analyzed for its plant nutrients such as nitrogen, phosphorous, potassium and other physical and chemical parameters. Experimental soil was tested for its chemical and physical parameters. The pulses seeds (Namadhari and Mayhco) were sowed in the prepared land and irrigated by using raw water, 50 and 33 % distillery spentwash. The impact of distillery spentwash on proximate principles (moisture, protein, fat, fibre, carbohydrate, energy, calcium, phosphorous and iron), vitamin content (carotene and vitamin C), mineral and trace elements (magnesium, sodium, potassium, copper, manganese, zinc, chromium and nickel) of pulses were investigated.